Transdisciplinary ethnography in india
1 online resource.
Keywords: This book familiarises readers with a new way to treat the subject of gender, foregrounding the real voices of women, their experiences doing ethnographic work, and their courage in sharing their stories publicly for the first time in the context of India. A useful companion to more theory-based anthropological studies, the book connects ethnographic data to what eventually becomes theories formed from the field. Chapters by women from a variety of disciplines - Anthropology, Literary and Translation studies, Political Sciences - transcend the academic boundaries between social sciences and humanities. The book shows how the researchers navigate in the field, write in ways that defy their academic life and work, and call into question their narrative voice. The book presents a space for women to reflecton their individual themes of research and at partially filling the vacuum mentioned above, the silences of women's voices and expressions. The experiences described in the chapters differ, both along the divide of a "native" and a non-"native" fieldworker and along different disciplinary fields, but they share the experience of a long-term fieldwork in India and the need to self-reflect on the impact of this experience on the way the field is represented, on the people encountered in the field, on the way the field impacted on the fieldworker. The book is a useful presentation of how female researchers act in the field as women and scholars. Filling a gap in the existing literature of ethnographic research methods, the book will be of interest to students and researchers interested in the fields of Gender Studies, Social Work, Sociology, Anthropology and Asian Studies.